Development of a technique for inductive measurement of laser-induced magnetization dynamics in thin films - Tomáš Ilit’; Pavol Valko; Milan Držík; Marianna Ušáková; Martin Šoka; Marian Marton; Miroslav Behúl; Marian Vojs (Metrology and Measurement Systems, 2019)
We present the development of a technique for studying laser-induced magnetization dynamics, based on inductive measurement. The technique could provide a simple tool for studying laser-induced demagnetization in thin films and associated processes, such as Gilbert damping and magnetization precession. It was successfully tested using a nanosecond laser and NiZn ferrite samples and – after further development – it is expected to be useful for observation of ultra-fast demagnetization. The combination of optical excitation and inductive measurement enables to study laser-induced magnetization dynamics in both thin and several micrometre thick films and might be the key to a new principle of ultrafast broadband UV–IR pulse detection.